2017
DOI: 10.1128/mcb.00596-16
|View full text |Cite
|
Sign up to set email alerts
|

Casein Kinase 2 Is Linked to Stress Granule Dynamics through Phosphorylation of the Stress Granule Nucleating Protein G3BP1

Abstract: Stress granules (SGs) are large macromolecular aggregates that contain translation initiation complexes and mRNAs. Stress granule formation coincides with translational repression, and stress granules actively signal to mediate cell fate decisions by signaling to the translation apparatus to (i) maintain translational repression, (ii) mount various transcriptional responses, including innate immunity, and (iii) repress apoptosis. Previous work showed that G3BP1 is phosphorylated at serine 149, which regulates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 62 publications
3
85
1
Order By: Relevance
“…It has been suggested that G3BP has both antiviral and proviral activities by activating PKR (95,96) and suppressing P1234 translation (97), that it escorts the incoming genomic RNA to the plasma membrane (37), and that it regulates the switch from translation to transcription of genomic RNA (91). G3BP1 is the target for several posttranslational modifications (e.g., phosphorylation, ADP ribosylation, acetylation, methylation, NEDDylation, and ubiquitylation) that regulate its endonuclease activity and its participation in the formation of stress granules and other protein complexes (94,(98)(99)(100)(101)(102)(103)(104)(105)(106)(107). The presence or absence and the location of these modifications likely also play a regulatory role in interaction with nsP3 and genomic RNA for initiation of alphavirus replication.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that G3BP has both antiviral and proviral activities by activating PKR (95,96) and suppressing P1234 translation (97), that it escorts the incoming genomic RNA to the plasma membrane (37), and that it regulates the switch from translation to transcription of genomic RNA (91). G3BP1 is the target for several posttranslational modifications (e.g., phosphorylation, ADP ribosylation, acetylation, methylation, NEDDylation, and ubiquitylation) that regulate its endonuclease activity and its participation in the formation of stress granules and other protein complexes (94,(98)(99)(100)(101)(102)(103)(104)(105)(106)(107). The presence or absence and the location of these modifications likely also play a regulatory role in interaction with nsP3 and genomic RNA for initiation of alphavirus replication.…”
Section: Discussionmentioning
confidence: 99%
“…Orf6 of SARS-CoV has been shown to play a role in antagonizing host interferon signaling 63 ; we identified a novel, high-confidence interaction between SARS-CoV-2 Orf6 and NUP98-RAE1, an interferon-inducible mRNA nuclear export complex 64 that is hijacked or degraded by multiple viruses, including VSV, Influenza-A, KSHV, and Polio, and is a restriction factor for Influenza-A infection 58,60,62,65 . The X-ray structure of VSV M protein complexed with NUP98-RAE1 66 reveals key binding interactions that include a buried methionine residue on the M-protein packing into a hydrophobic pocket in RAE1, as well as neighboring acidic residues interacting with a basic patch on the NUP98-RAE1 complex (Fig 4b).…”
Section: Sars-cov-2 Interacts With Multiple Innate Immune Pathwaysmentioning
confidence: 97%
“…In contrast, the SGs induced by chronic starvation lack rps6 ( Fig.2A) (Kedersha et al 2002), suggesting that small ribosomal subunits are excluded from these structures. We therefore performed RNA FISH for 18S and 28S ribosomal RNA in cells subjected to both acute oxidative stress and chronic nutrient starvation ( Fig.2B,C) (Kedersha et al 2002;Kedersha et al 2016;Sfakianos et al 2018;Reineke et al 2017;Tsai et al 2016). Surprisingly, while 18S rRNA was strongly localized to arsenite-induced SG, 18S was weak or absent in nutrient starvationinduced SG (Fig.2B,C).…”
Section: Resultsmentioning
confidence: 99%
“…Starvation proceeded in accordance with the above description followed by fixation in PBS with 4 % formaldehyde for 30 min. Cells were permeablized in PBS with 0.5 % triton x-100 followed by blocking with 5% BSA in PHEM buffer (Reineke et al 2017). Cells were stained with antibodies against G3BP1 ( (Reineke et al 2012), or Santa Cruz, Dallas, TX, H10), eIF3b (Santa Cruz, Dallas, TX, N20), HuR (Santa Cruz, Dallas, TX, 3A2), Tia1 (Santa Cruz, Dallas, TX, C20), or rps6 (Cell Signaling, Danvers, MA, 5G10), and mounted with medium containing DAPI (Vector labs, Burlingame, CA).…”
Section: Immunofluorescence Microscopymentioning
confidence: 99%
See 1 more Smart Citation